Shell model calculations of the nuclear structure in the ``island of inversion'' N=20 region: Na-31,Na-33,Na-35 isotopes - Ahmed, Firas A. (2022)
The unmixed intruder configurations (2p-2h) were studied for (31)'(33)'Na-35 isotopes inside the island of inversion within the SDPF-U Hamiltonian with restrictions. The proton's positions that give a good correlation energy were determined for the first time. The unmixed intruder configurations (2p-2h), in addition of the proton's positions, were found using the restriction technique. The proposed restricted configurations were applied to calculate the low-lying states and probabilities of the transitions B(E2 : 0(1)(+) -> 2(1)(+)) with effective charges e(p) = 1.3e and e(n) = 0.537e for the Na-31,Na-33,Na-35 isotopes. Moreover, the outcomes of this work compared reasonable well to the available experimental results. The good agreement between the theoretical and the experimental values, especially for the first three positive states 3/2, 5/2 and 7/2, confirmed the domination of unmixed (2p_2h) intruder configurations in the ground states for these nuclei. On the basis of this agreement, two positive states (9/2, 1/2) are suggested in this paper. Furthermore, the theoretical results showed the accuracy of SDPF-U Hamiltonian in calculations for this region (N=20).